O governo João Goulart nas páginas da Folha de S. Paulo - Almeida, Cristiane Rodrigues Soares (2008)
Along this work, I discussed - from the relationship story / press - the Folha de São Paulo newspaper interpretations on the corresponding period of Joao Goulart s government (1961-1964). This newspaper reverberated on its pages various issues related to that government, sometimes for or against, and had participated in the political and ideological debates that boiled frequently during that period. And, above all, engaged in the construction of a determined representation of that particular historical moment. The present research is to check through the article in this newspaper about the representation it has built in that period. It intend to show how the Folha de São Paulo portrayed this given context and what is its position concerning the political projects proposed by Joao Goulart and its participation in the outcome of his deposal. Linked to this discussion I analyze the press issue along with its tactics and articulations highlighting its role as a channel of expression of political interests, and ideological supporters.